PENGARUH INTEGRITAS DAN KREATIVITAS KONSULTAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Katuuk, Djuliana; Manossoh, Hendrik; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2017)
Taxes have a major influence on state revenues. With the tax system in Indonesia is considered to have a high complexity of the number of regulations that often change from time to time make taxpayers need other parties to conduct self assessment system that is tax consultant. Tax consultants as professionals who offer services in the field of taxation should have the creativity in this case solves the problem of taxation of clients but cannot be separated from it must be integrity according to ethical principles.The purpose of this study is to determine the influence of the integrity and creativity of tax consultants simultaneously and partially to taxpayer compliance. Respondents in this study are taxpayers users of tax consultant services in Manado. Analytical technique in this study using multiple regression analysis using quantitative data with survey approach using questionnaires research instrument with the sample used as much as 48 respondents. Based on the statistical test, the results of this study indicate that the tax consultant's integrity and creativity of tax consultants simultaneously and partially have an influence on taxpayer compliance. So it can be concluded Tax Consultant has influence in improving taxpayer compliance.Keywords : Integrity, Creativity, Tax Consultant, Taxpayer Compliance